The Self-Actualization of the Main Character in the Novel Anak Rantau by Ahmad Fuadi - Pahlewi, Indra Putra; Nuryatin, Agus; Luriawati, Deby (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The novel Anak Rantau by Ahmad Fuadi was chosen as the object of research because of the many aspects of self-actualization that are raised in the story, especially regarding the main character's struggles in facing the realities of life and its twists.. The purpose of this research was to describe and explain the process and characteristics of the main character's self-actualization in the novel Anak Rantau by Ahmad Fuadi. This study used a literary psychology approach. The psychological theory used was Abraham Maslow's self-actualization. Hepi started the process of self-actualization since he was abandoned in Tanjung Duren village by his father. Hepi fulfilled 14 traits of self-actualization. The nature of self-actualization that he has was 1) efficient observation of reality; 2) self-acceptance and others as they are; 3) spontaneity, simplicity, and reasonableness; 4) focus on the problem; 5) the need for privacy; 6) function autonomously; 7) appreciation that is always fresh; 8) social awareness/interest; 9) interpersonal relationships; 10) democratic; 11) differences between means and objectives; 12) creativity; 13) independence, and 14) peak experience.